Excitatory Repetitive Transcranial Magnetic Stimulation Over Prefrontal Cortex in a Guinea Pig Model Ameliorates Tinnitus - Zimdahl, Jack W.; Thomas, Harrison; Bolland, Samuel J.; Leggett, Kerry; Barry, Kristin M.; Rodger, Jennifer; Mulders, Wilhelmina H. A. M. (Frontiers in Neuroscience, 2021)
Tinnitus, a phantom auditory perception that can seriously affect quality of life, is generally triggered by cochlear trauma and associated with aberrant activity throughout the auditory pathways, often referred to as hyperactivity. Studies suggest that non-auditory structures, such as prefrontal cortex (PFC), may be involved in tinnitus generation, by affecting sensory gating in auditory thalamus, allowing hyperactivity to reach the cortex and lead to perception. Indeed, human studies have shown that repetitive transcranial magnetic stimulation (rTMS) of PFC can alleviate tinnitus. The current study investigated whether this therapeutic effect is achieved through inhibition of thalamic hyperactivity, comparing effects of two common clinical rTMS protocols with sham treatment, in a guinea pig tinnitus model. Animals underwent acoustic trauma and once tinnitus developed were treated with either intermittent theta burst stimulation (iTBS), 20 Hz rTMS, or sham rTMS (10 days, 10 min/day; weekdays only). Tinnitus was reassessed and extracellular recordings of spontaneous tonic and burst firing rates in auditory thalamus made. To verify effects in PFC, densities of neurons positive for calcium-binding proteins, calbindin and parvalbumin, were investigated using immunohistochemistry. Both rTMS protocols significantly reduced tinnitus compared to sham. However, spontaneous tonic firing decreased following 20 Hz stimulation and increased following iTBS in auditory thalamus. Burst rate was significantly different between 20 Hz and iTBS stimulation, and burst duration was increased only after 20 Hz treatment. Density of calbindin, but not parvalbumin positive neurons, was significantly increased in the most dorsal region of PFC indicating that rTMS directly affected PFC. Our results support the involvement of PFC in tinnitus modulation, and the therapeutic benefit of rTMS on PFC in treating tinnitus, but indicate this is not achieved solely by suppression of thalamic hyperactivity.